2021
DOI: 10.1002/jnr.24899
|View full text |Cite
|
Sign up to set email alerts
|

A multielectrode array‐based hypoxia model for the analysis of electrical activity in murine retinae

Abstract: Several eye diseases, for example, retinal artery occlusion, diabetic retinopathy, and glaucoma, are associated with retinal hypoxia. The lack of oxygen in the retina, especially in retinal ganglion cells (RGCs), causes cell damage up to cell degeneration and leads to blindness. Using multielectrode array recordings, an ex vivo hypoxia acute model was established to analyze the electrical activity of murine wild‐type retinae under hypoxic stress conditions. Hypoxia was induced by exchanging the perfusion with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
(58 reference statements)
1
5
0
Order By: Relevance
“…The effect of hypoxic stress on the functionality and survival of RGCs has been demonstrated in our previous work (Ingensiep et al, 2021) as well as in multiple other studies (Gross et al, 1999;Kergoat et al, 2006;Janaky et al, 2007;Tan et al, 2011). RGCs transit into a stress mode, even after short-time hypoxia, where no spontaneous electrical activity and no response to electrical or light stimuli can be recorded.…”
Section: Introductionsupporting
confidence: 67%
See 3 more Smart Citations
“…The effect of hypoxic stress on the functionality and survival of RGCs has been demonstrated in our previous work (Ingensiep et al, 2021) as well as in multiple other studies (Gross et al, 1999;Kergoat et al, 2006;Janaky et al, 2007;Tan et al, 2011). RGCs transit into a stress mode, even after short-time hypoxia, where no spontaneous electrical activity and no response to electrical or light stimuli can be recorded.…”
Section: Introductionsupporting
confidence: 67%
“…Although high IOP is considered the main risk factor in glaucoma, we showed that the sheer mechanical stress of pressure does not seem to affect the retinal functionality in the acute model. In contrast, we showed that hypoxic stress has a dramatic effect on the RGCs' electrical activity and their survival rate (Ingensiep et al, 2021). Hypoxia can be induced in vivo by impaired blood flow under high IOP (Andreeva et al, 2014;Wiemann et al, 2021).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Primarily, explanted retinas lack the metabolic environment of the eye, and some of its electrophysiological properties under ex vivo conditions may be distorted. For example, identifying stimulation parameters for retinal implant performance optimization may depend on retina metabolic conditions (Ingensiep et al, 2021) and retina explant viability (Balasubramanian and Shabanian, 2020). Therefore, ex vivo stimulation studies, for example, may provide only a partial picture of retinal response to electrical stimulation.…”
Section: What Can Be Further Gained From a Bidirectional Communicatio...mentioning
confidence: 99%